Effects of feeding ration incorporating Piliostigma thonningii (schum.) pods on growth and gastrointestinal parasites in West African Dwarf goats of Burkina Faso - Dindané-Ouédraogo, Safoura; Ouédraogo-Koné, Salifou; Ouédraogo, Dominique; Ima, Issouf; Zoma-Traoré, Bienvenue; Soudre, Albert (International Journal of Environment, Agriculture and Biotechnology, 2021)
The objective of this study was to determine the availability and the use of Piliostigma thonningii pods through individual interviews using semi-structured questionnaires, and to evaluate the effect of diet incorporating these pods on growth and parasitic status of goats. The trial consisted in feeding diets to 12 adult West African dwarf goats, divided into three batches of four animals each. Batches 1 and 2 received a diet with 40% Piliostigma thonningii pods, and bamboo charcoal as a zootechnical additive (1g/kg PV) in the diet of batch 2. For batch 3, the animals received a diet without the pods, proportionally replaced by cotton seed cake. The experiment lasted for 78 days including two weeks of adaptation. The Mac-Master technique was used for identification and enumeration of strongyle eggs and coccidia oocysts. The results showed a higher frequency of the use of pods in shredded form (38.18%) compared to crushed (25.45%) and whole (20.00%). The availability of pods was confirmed by 57.1% of the respondents. The ADG obtained with the batches fed diet incorporating the pods were 16.39±4.10 and 24.01±5.97 g/d for batches 1 and 2 respectively, significantly lower than those obtained with the animals in batch 3 that received the cotton seed cake (31.39±5.80 g/d). The level of EPG recorded in animals from batch 1 (50±100) was significantly lower than those obtained with animals from batches 2 and lot 3 (500±455 and 925±736 respectively). The use of Piliostigma thonningii pods could be of great use in goat intensive production improvement programs.